Stimulus - Job Satisfaction Relationship Survey on Bank and Financial Institution Supervisors in Nepal - Acharya, Shankar Prasad (Administration and Management Review, 2009)
This paper is a Stimulus-Job Relationship Survey of Bank and Financial Institution supervisors in Nepal. General matters discussed about in this paper relate to (i) the extent of contribution of different motivating variables like pay, company policy, environment and job satisfaction in the work place, (ii) the role of supervisors' family size, income, age structure or service tenure in stimulating the motivating variable and (iii) the corrective measures to be undertaken to lever up the overall motivation level of the financial institution supervisors. The Human Resource Development (HRD) policy essential for the Human Resource Management (HRM) practices can clearly be discerned from this study report. Administration and Management Review Vol. 21, No. 1, January, 2009, Page 58-101